PS 07-01 EFFECT OF EXERCISE TRAINING ON BDNF AND TrkB IN THE HIPPOCAMPUS IN SPONTANEOUSLY HYPERTENSIVE RATS. (September 2016) - Lee, Heow Won; Maltez, Melissa; Wang, Tao; Wang, Hongwei; Ahmad, Monir; Leenen, Frans H.H.
Abstract : Objective: Hypertension decreases neuronal plasticity and survival in the hippocampus, contributing to cognitive impairment. Brain-derived neurotrophin factor (BDNF) plays an important role in neuronal plasticity and neurogenesis in the dentate gyrus (DG) of the hippocampus. Exercise training up-regulates BDNF in the hippocampus, and improves neurogenesis and cognitive function. It is unclear whether exercise-induced activation of BDNF in the hippocampus also occurs in hypertensive rats, associated with decrease in blood pressure (BP). Therefore, the effects of exercise training on BDNF and its binding receptor tropomyosin-related kinase B (TrkB) mRNA were assessed in the hippocampus of spontaneously hypertensive rats (SHR). Design and Method: SHR (SHR-ExT, n = 7) and normotensive Wistar-Kyoto (WKY) rats (WKY-ExT, n = 9) were trained using a moderate-intensity exercise treadmill program for 5 weeks. Sedentary SHR (n = 6) and WKY rats (n = 10) were included as controls. At the end, systolic BP (SBP) and diastolic BP (DBP) were measured and the brains were collected. DG and CA regions of the hippocampus were micro-punched separately, and BDNF and TrkB mRNA were assessed by real-time PCR. Results: SHR had significantly higher BP compared to WKY. In SHR, BDNF mRNA was decreased in the DG, but not in the CA regions. In contrast, TrkB mRNA was increased in both the DG and CA regions. Exercise decreased BP of SHR. BDNF mRNA was increased in the DG compared to SHR-Sed, but there are no effects of exercise in CA regions. Exercise had no effect on TrkB mRNA in DG and CA regions. BDNF mRNA in the DG correlated inversely with SBP (r = −0.66, p < 0.01) and DBP (r = −0.71, p < 0.01). Conclusions: Exercise normalizes decreased BDNF mRNA in the DG of SHR, and this improvement may contribute to its beneficial effects on cognitive function.